Case of Angular Blepharitis Caused by Demodex folliculorum. Issue 3 (September 2021) - Luo, Susan; Burkat, Cat; van Landingham, Suzanne W.
Angular blepharitis is inflammation of the eyelid skin at the lateral canthus, most commonly caused by Staphylococcus and Moraxella species. The Demodex mite is an external parasite that often infests the human eyelid margin and has been implicated in both anterior and posterior blepharitis. The authors describe the case of a 43-year-old female who presented for evaluation of a 3-month history of bilateral canthal eyelid irritation, consistent with angular blepharitis. This is a case report and review of relevant literature. Skin biopsy showed evidence of Demodex folliculorum infestation. Multiple D. folliculorum organisms were visualized within the hair follicles and on the surface, along with pockets of acute and chronic nongranulomatous inflammation surrounding hair follicles. The patient was treated with tea tree oil applied to her eyelids and eyelashes twice daily with complete resolution of symptoms. To our knowledge, this is the first report of angular blepharitis with histopathologic confirmation of Demodex infestation. In this discussion, we cover manifestations of the Demodex mite, angular blepharitis, and treatment options. Due to the lack of literature regarding this entity, we feel that it may be an underrecognized periocular and dermatologic condition that can lead to misdiagnosis, visits to multiple practitioners, and significant functional and cosmetic sequelae to the patient. Demodex infestation should be considered on the differential diagnosis for cases of refractory angular blepharitis, particularly when unresponsive to topical steroids. Based on results from treating Demodex anterior and posterior blepharitis and this case, treatment with tea tree oil should be considered.